PENGARUH DISIPLIN PENGENDARA KENDARAAN BERMOTOR TERHADAP KESELAMATAN BERLALU LINTAS DI KOTA BOGOR - Turohman, Rahmat Saepul; Iskandar, Abubakar; seran, M.YGG (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2017)
The purpose of this study are to describe the discipline of motor vehicle drivers in traffic and the level of traffic safety in Bogor City, to analyze the effect of discipline motorists against motor vehicle safety in Bogor, to describes the efforts undertaken Bogor City Government cq. DLLAJ city of Bogor in improving discipline of motorists against motor vehicle safety in Bogor. Methods used are descriptive and associative method. The data used are primary data and secondary data. Primary data is collected by distributing a questionnaire, and supported by the observations and interviews. The collection of secondary data sourced from documents, literature and related research. The sampling technique is simple random sampling that amounted to 56 motorists on the three streets are: Jl.Raya Tajur as many as 20 riders, 16 riders from Jl.KS Tubun, and 20 riders from Jl.Jalak Harupat. Based on the correlation coefficient between the disciplines of motor vehicles with safety in traffic amounted to 0.513 and the interpretation is quite strong, and the positive direction indicates that the variable of riders discipline with variable of safety is significant correlation, means that the higher discipline the higher the level of safety. That correlation between the variable X (Discipline) with Y (Safety) is significant at an error rate of 0.01 (1%) and 99% confidence. Based on the conclusion, the author recommend: the Department of Transportation in Bogor through the Section of Communication, Information, Education and Communications-Section Guidance and Safety in order to continue disseminating safety riding, and equipping of road infrastructure such as mounting traffic signs, road markers, tool of speed limit, a safety device road users to improve road safety. Keywords: High-Discipline, safety drive, the higher discipline the higher the level of safety